(untitled) (Scientific journal of the Fergana State University, 2024)
This article presents the results of experiments conducted to establish the effect of the drug on the environment and human health, based on furfural, urea, and zinc acetate, which has shown high biological activity in plant growth, development, and combating diseases. The parameters of the drug‘s toxicity level, cumulative properties, chronic toxicity, permissible standards in water and air have been determined.